Extracellular Sphingomyelinase Rv0888 of Mycobacterium tuberculosis Contributes to Pathological Lung Injury of Mycobacterium smegmatis in Mice via Inducing Formation of Neutrophil Extracellular Traps - Dang, Guanghui; Cui, Yingying; Wang, Lei; Li, Tiantian; Cui, Ziyin; Song, Ningning; Chen, Liping; Pang, Hai; Liu, Siguo (Frontiers in Immunology, 2018)
Mycobacterium tuberculosis is the causative agent of tuberculosis (TB), which mainly causes pulmonary injury and tubercles. Although macrophages are generally considered to harbor the main cells of M. tuberculosis, new evidence suggests that neutrophils are rapidly recruited to the infected lung. M. tuberculosis itself, or its early secreted antigenic target protein 6 (ESAT-6), can induce formation of neutrophil extracellular traps (NETs). However, NETs trap mycobacteria but are unable to kill them. The role of NETs’ formation in the pathogenesis of mycobacteria remains unclear. Here, we report a new M. tuberculosis extracellular factor, bifunctional enzyme Rv0888, with both nuclease and sphingomyelinase activities. Rv0888 sphingomyelinase activity can induce NETs’ formation in vitro and in the lung of the mice and enhance the colonization ability of Mycobacterium smegmatis in the lungs of mice. Mice infected by M. smegmatis harboring Rv0888 sphingomyelinase induced pathological injury and inflammation of the lung, which was mainly mediated by NETs, induced by Rv0888 sphingomyelinase, associated protein (myeloperoxidase) triggered caspase-3. In summary, the study sheds new light on the pathogenesis of mycobacteria and reveals a novel target for TB treatment.